Sport Marketing - Dees, Windy, 1977-; Walsh, Patrick, 1978-; McEvoy, Chad D., 1971-; McKelvey, Stephen, 1959-; Mullin, Bernard James; Hardy, Stephen, 1948-; Sutton, William Anthony, 1951- (Human Kinetics, Inc., 2022)
"This book helps students prepare for careers in the fast-paced world of sport marketing, as well as provides a resource for practitioners looking for the latest information in the field. The book offers abundant examples of the latest issues in the competitive marketplace"--